Competition: Theoretical and Practical Aspects on the Example of the Republic of Belarus - O. V. Sinyak (Цифровая трансформация, 2020)
The article considered the theoretical and practical examples of the Republic of Belarus on the development ofcompetition, the role of competition in the life of society is indicated. Definitions of the term «competition» are given. A brief description of the types of market structures is given: perfect competition, monopolistic competition, oligopoly, monopoly. The mechanism of development of competition in the Republic of Belarus at the present stage is considered, including through the creation of an antimonopoly structure, ifs goals, objectives, ongoing efforts to develop competition, adjust the regulatory framework, international experience, etc. The directions that promote competition have been identified: improving legislation, expanding the powers of the antimonopoly structure, further developing preventive institutions of antimonopoly regulation, advocating competition, developing exchange trading, etc. The development of competition is a tool to achieve the goals of social-economic development of the country.